DEMAND STRUCTURE ANALYSIS AND BALANCE OF PAYMENTS INDONESIA AND CHINA EXPORT-IMPORT - Indria Mayesti; Mukti Mukti; Ardi Afrizal (International Journal of Artificial Intelligence Research, 2022)
The purpose of this research is to use the growth rate model and the ratio value of secondary data to analyze the Structure of Demand (% of GDP at current market prices) for the value of Indonesia's exports of goods and services to China, where China is 0.6% ahead of 3.40% compared to Indonesia 2.80% while for the Balance of Paymant value, Indonesia is 1.10% superior from 5.20% compared to China at 4.10% and for the ratio value between Indonesia, it is 1.60% superior from 2.40% compared to China at 0,80%. From the results of the research, the general advice of researchers is that Indonesia needs to improve the structure of export and import demand so that it continues to increase the country's income as listed in Indonesia's trade balance